2023
DOI: 10.3390/antibiotics12091446
|View full text |Cite
|
Sign up to set email alerts
|

Detection, Identification and Diagnostic Characterization of the Staphylococcal Small Colony-Variant (SCV) Phenotype

Karsten Becker

Abstract: While modern molecular methods have decisively accelerated and improved microbiological diagnostics, phenotypic variants still pose a challenge for their detection, identification and characterization. This particularly applies if they are unstable and hard to detect, which is the case for the small-colony-variant (SCV) phenotype formed by staphylococci. On solid agar media, staphylococcal SCVs are characterized by tiny colonies with deviant colony morphology. Their reduced growth rate and fundamental metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 90 publications
(125 reference statements)
0
6
0
Order By: Relevance
“…In this context, macrophage and neutrophil assays would be valuable for assessing both the extent of immune response and the presence of persistent cells. Moreover, the determination of the auxotrophism (13, 17) of K. pneumoniae SCVs and of the molecular mechanisms that drive SCV formation and the resulting antibiotic resistance in this species require further investigation. Integrating a comprehensive range of approaches encompassing genomics, transcriptomics, and proteomics, the utilization of experimental evolutionary models can yield valuable insights into the genetic determinants and regulatory networks orchestrating SCV phenotypes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, macrophage and neutrophil assays would be valuable for assessing both the extent of immune response and the presence of persistent cells. Moreover, the determination of the auxotrophism (13, 17) of K. pneumoniae SCVs and of the molecular mechanisms that drive SCV formation and the resulting antibiotic resistance in this species require further investigation. Integrating a comprehensive range of approaches encompassing genomics, transcriptomics, and proteomics, the utilization of experimental evolutionary models can yield valuable insights into the genetic determinants and regulatory networks orchestrating SCV phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Another non-classical mechanism leading to functional resistance is the formation of the small colony variant (SCV) phenotype. SCVs are subpopulations of bacteria that exhibit slow growth, reduced colony size, and altered phenotypic properties compared to their normal-growing counterparts, making them difficult to detect and treat effectively (12, 13). Their ability to evade the host’s immune surveillance and to undermine the effectiveness of antimicrobial interventions by host cell internalization results in intracellular persistence, which contributes significantly to the recurrence and chronicity of the infection (14, 15).…”
Section: Introductionmentioning
confidence: 99%
“…Since the formation of S . aureus SCVs are usually linked with deficiencies in the utilization of menadione, hemin or thymidine by bacteria, we conducted the auxotrophism test on the induced SCVs to find the possible mechanisms [ 12 ]. The results showed that the colony sizes of the 3 induced SCVs strains on MH plates supplemented with each compound separately were not significantly different from those on the plates without these agents, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, macrophage and neutrophil assays would be valuable for assessing both the extent of immune response and the presence of persistent cells. Moreover, the determination of the auxotrophism ( Kriegeskorte et al., 2014 ; Becker, 2023 ) of K. pneumoniae SCVs and of the molecular mechanisms that drive SCV formation and the resulting antibiotic resistance in this species require further investigation. Integrating a comprehensive range of approaches encompassing genomics, transcriptomics, and proteomics, the utilization of experimental evolutionary models can yield valuable insights into the genetic determinants and regulatory networks orchestrating SCV phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Another non-classical mechanism leading to antibiotic tolerance is the formation of the small colony variant (SCV) phenotype. SCVs are subpopulations of bacteria that exhibit slow growth, reduced colony size, and altered phenotypic properties compared to their normal-growing counterparts, making them difficult to detect and treat effectively ( Proctor et al., 2006 ; Becker, 2023 ). Their ability to evade the host’s immune surveillance and to undermine the effectiveness of antimicrobial interventions by host cell internalization results in intracellular persistence, which contributes significantly to the recurrence and chronicity of the infection ( Tuchscherr et al., 2011 ; Kahl et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%